Medieval Buda in context - Nagy, Balázs (Brill's companions to European history ;, 2016)
"Medieval Buda in Context discusses the character and development of Buda and its surroundings between the thirteenth and the sixteenth centuries, particularly its role as a royal center and capital city of the medieval Kingdom of Hungary. The twenty-one articles written by Hungarian and international scholars draw on a variety of primary sources: texts, both legal and literary; archaeological discoveries; architectural history; art history; and other studies of material culture. The essays also place Buda in the political, social, cultural and economic context of other contemporary central and eastern European cities. By bringing together the results of research undertaken in recent decades for an English-language readership, this volume offers new insights into urban history and the culture of Europe as a whole. Contributors are János M. Bak, Zoltán Bencze, Judit Benda, István Draskóczy, Antonín Kalous, István Kenyeres, Gábor Klaniczay, András Kubinyi, József Laszlovszky, Károly Magyar, Balázs Nagy, Szilárd Papp, James Plumtree, Martyn Rady, Valery Rees, Orsolya Réthelyi, Beatrix F. Romhányi, Enikő Spekner, Péter Szabó, Katalin Szende, András Vadas, András Végh, and László Veszprémy."--Provided by publisher.